Flavor, satiety and food intake - Tepper, Beverly J. (IFT Press series, 2017)
This unique book provides a comprehensive review of the latest science on a key aspect of appetite control. It brings together contributions by leading researchers worldwide who approach this complex, multifaceted issue from a variety of differing perspectives, including those of food science, psychology, nutrition, and medicine, among others. It is well known that products that require greater oral processing tend to be more sating. At the same time, the orosensory exposure hypothesis holds that flavor and texture in the mouth are critical in determining meal-size. They may act as key predictors of nutritional benefits and so promote better processing of foods. These two related ideas are at the forefront of current thinking on flavor-satiety interactions. Yet, until Flavor, Satiety and Food Intake no book has offered an integrated treatment of both concepts. The only single-source reference of its kind, it brings health professionals, product developers, and students up to speed on the latest thinking and practices in this fascinating and important area of research.--Provided by publisher.